English in China: Language, Identity, and the Ti–Yong Principle in an Era of Globalization - Dan Zhang (Universitas Negeri Surabaya, 2025)
China’s relationship with English has long been shaped by history, globalization, and questions of identity. Once stigmatized as a symbol of Western aggression during the Opium Wars and unequal treaties, English later came to be justified through the ti–yong principle, Chinese learning for essence, Western learning for utility, which positioned it as a useful tool but not a cultural threat. Since the Reform and Opening-up of 1978, and especially after China’s accession to the WTO in 2001 and the Beijing Olympics in 2008, English has become central to modernization, education, and international participation. Yet this expansion has also intensified debates about cultural integrity and national selfhood. This study investigates perceptions of English among high school students, university students, teachers, and parents in Beijing, employing Q methodology supported by semi-structured interviews and critical discourse analysis. Four shared viewpoints were identified: English as modernization and global mobility, cultural protectionism anchored in ti–yong, pragmatic bilingual complementarity, and anxiety over cultural dilution. Findings suggest that while the ti–yong principle remains a powerful reference point, its interpretation varies from strict hierarchical separation of cultural essence and linguistic utility to more hybrid orientations that embrace translanguaging and the legitimacy of China English. The study contributes to applied linguistics and identity research by showing how English in China simultaneously functions as global capital and a contested cultural symbol, and it argues for policies and pedagogies that enable learners to engage internationally without compromising cultural authenticity.